PROBLEMATIKA ISBAT NIKAH DAN PENYELESAIANNYA DI PENGADILAN AGAMA KABUPATEN JEPARA - Mufidah, Alimatul; Choeri, Imron; Rosyada, Amrina (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2025)
Marriage in Islam is a sacred bond recognized by law and religion, but many marriages are not officially recorded, necessitating marriage validation (isbat nikah) for legal recognition. This study aims to identify the challenges in implementing isbat nikah and the mechanisms for resolving them at the Jepara Regency Religious Court, as well as to analyze the applied Islamic law and positive law approaches. Using a descriptive-analytical qualitative approach, data were collected through in-depth interviews with judges, clerks, and petitioners, non-participatory observation of court proceedings, and document analysis of 15 isbat nikah case files from 2022–2023. Data analysis followed the Miles and Huberman interactive model, involving data reduction, presentation, and conclusion drawing with verification through triangulation. The findings reveal key issues, including low legal literacy among the public, particularly regarding witness and document requirements, and limited access to legal services and e-Court technology, with isbat nikah requests being reactive for administrative purposes. The Jepara Religious Court addresses these issues through educational approaches, tolerance for incomplete evidence, and collaboration with village governments, guided by Law No. 1 of 1974 (amended by Law No. 16 of 2019) and the Compilation of Islamic Law. The discussion highlights that this approach reflects the principle of maslahah, but challenges in legal literacy and technology access require cross-institutional collaborative strategies to enhance the effectiveness of isbat nikah and public legal awareness